Swans, Falling Bodies and Five-Legged Dogs - Collard, D. A. (Quarterly Journal of Economics, 1964)
Journal Article Swans, Falling Bodies and Five-Legged Dogs Get access D. A. Collard D. A. Collard University College, Cardiff Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 78, Issue 4, November 1964, Pages 645–646, https://doi.org/10.2307/1879661 Published: 01 November 1964